Exploring the inequality of opportunities in South Africa - Little, Megan (School of Economics, 2015)
This paper constructs an Inequality of Opportunities framework for South Africa and seeks to establish whether earnings inequality therein has been driven by differing circumstances or variations in efforts. The analysis has been performed on a 2008 cross-sectional South African dataset, proxying for circumstances using years of parental education and for efforts using an individual's own education in years.